2021
DOI: 10.1021/acsaem.1c01332
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Performance, and Long-Term Stability of Nanostructured Ni-YSZ Thin Film Electrodes

Abstract: Nickel and yttria-stabilized zirconia (YSZ) composite anodes were fabricated by a powder-free, polymeric precursor-based process, in which Ni, Y, and Zr cations are redistributed by phase separation at the nanoscale, forming YSZ and Ni(O). Transmission electron microscopy/energy-dispersive X-ray spectroscopy analyses revealed for the first-time in the literature that the nanocomposite thin film Ni-YSZ anodes had microstructures consisting of alternating Ni and YSZ nanolayers. A pre-calcination step applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It has been reported that complex and tortuous YSZ network can impede Ni movement and can hinder Ni coarsening. 52 Another difference comes from the fabrication process. In the present study, Ni stripes are sputtered on the YSZ substrate, while Ni/YSZ cermet are fabricated through wet ceramic processes such as screen printing, slurry spraying, or tape casting of NiO and YSZ powders, followed by high-temperature sintering.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that complex and tortuous YSZ network can impede Ni movement and can hinder Ni coarsening. 52 Another difference comes from the fabrication process. In the present study, Ni stripes are sputtered on the YSZ substrate, while Ni/YSZ cermet are fabricated through wet ceramic processes such as screen printing, slurry spraying, or tape casting of NiO and YSZ powders, followed by high-temperature sintering.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ni-based composites have several drawbacks. For example, Ni de-wets YSZ surface due to the high interfacial energy, which enables coarsening and migration of Ni, resulting in a shortened electrochemically active electrocatalyst-ionic conductor-gas triple phase boundary and thus, perfor-mance loss [1,2]. Ni is also prone to oxidation to NiO when the fuel gas flow is interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…One of them may be the development of SOFCs that can operate directly with hydrocarbons, which possess an already well-developed supply service. Traditional Ni–YSZ cermets are recognized as the state-of-the-art material when operated on hydrogen owing to the unbeatable trade-off between the low cost of the materials and their great performances. However, the activity of Ni toward the formation of carbon leads to the poisoning of the anode by coking, affecting long-term operation. …”
Section: Introductionmentioning
confidence: 99%